EARLY CHILDHOOD MATHEMATICS COMMUNICATION IN REASONING AND APPLICATION OF MATHEMATICS THROUGH THE NUMBERS BOTTLE GAME IN Kindergarten ANNUR 2 KARANGTENGAH DEMAK - Aliyah (Schola, 2023)
Mathematical communication ability in learning mathematics is something that is needed by every student in order to facilitate the teaching and learning process.. While the number bottle game is a visual medium that can stimulate children's intelligence and memory in understanding number symbols. This study aims to describe early childhood mathematical communication in the application and mathematical proof through the number bottle game at Annur 2 Kindergarten Karangtengah Demak. This research uses qualitative method with descriptive research type. The subjects in this study were 15 students of group A TK Annur 2 who were selected through student results in math games. The method of collecting data is through observation, interviews, and documentation. The data were analyzed qualitatively by using the method of reduction, data assessment, and drawing conclusions. The results of the study show that in developing children's mathematical logic through the application of the number bottle game, they are as follows: a). Children are able to recognize numbers 1-10, b). The child is able to name the numbers 1 – 10, c). Children are able to sort numbers 1 – 10, d). The child is able to put objects into the number bottle according to the numbers listed on the number bottle and e). Children are able to do simple additions 1-10. So the writer can conclude that the teacher's role in developing mathematical logic through the implementation of steps in developing early childhood mathematical logic through number card games has shown optimal results.